The NAFTA tide: Lifting the larger and better boats - Angel Calderon-Madrid; Alexandru Voicu (Institute for the Study of Labor (IZA), 2007)
We use panel data on Mexican manufacturing plants to study the connection between plants' responses to changes in the economic environment and their contributions to aggregate productivity growth in the period following the implementation of the North American Trade Agreement (NAFTA). In all industries, an overwhelming share of aggregate productivity growth is accounted for by a small number of plants which were larger and more productive before the implementation of NAFTA and expanded and became more productive following the implementation of NAFTA. Plants that exported before NAFTA and export continuously through 2000 and some of the new exporters are more likely to be among the top-performing plants. Exporting activity and performance of plants with similar exporting experience, however, display remarkable heterogeneity. This heterogeneity implies that trade liberalization provided growth opportunity to larger and more productive plants irrespective of their export status and provides an explanation for the lackluster average productivity performance of exporting plants.
Keywords: C13; 330; NAFTA; trade liberalization; productivity; heterogeneity of plant-level performance; Außenhandelsliberalisierung; Verarbeitendes Gewerbe; Produktivität; Wirtschaftliche Anpassung; NAFTA-Staaten; Mexiko